Great Debate: Triple antithrombotic therapy in patients with atrial fibrillation undergoing coronary stenting should be limited to 1 week . (4th August 2022) - De Caterina, Raffaele; Agewall, Stefan; Andreotti, Felicita; Angiolillo, Dominick J; Bhatt, Deepak L; Byrne, Robert A; Collet, Jean-Philippe; Eikelboom, John; Fanaroff, Alexander C; Gibson, C Michael; Goette, Andreas; Hindricks, Gerhard; et al.
Graphical Abstract: Graphical abstract Key points in favour or against the use of one-week triple antithrombotic therapy for the majority of patients with AF and ACS/PCI. Abbreviations: TT, triple antithrombotic therapy; OAC, oral anticoagulant; DAPT, dual antiplatelet therapy; RCT, randomised controlled trials; ACS, acute coronary syndrome; PCI, percutaneous coronary intervention.